EFFECT OF CULTURE MEDIA ON GROWTH, COLONY CHARACTER AND SPORULATION OF THREE FOLIAR PATHOGENS OF GUAVA - N. K. MISHRA; B. P. TRIPATHI (The Bioscan, 2015)
The mycelial growth rate (radial and biomass), colony character and sporulation pattern of three folier pathogens of guava viz., Pestalotiapsidii, Colletotrichum gloesporides, Botriodiplodia theobromae) were observed on six different culture media after seven days of incubation at 25±2ºC. The six different culture media used were namely, Potato Dextrose (PDA), Czapek’sDox (CD), Richard’s (RM), Oat meal (OMA), Mature and Immature Guava Fruit extract Agar medium. The culture growth, characteristics (texture, surface, reverse colouration and zonation) and sporulation of three test fungi were significantly influenced by the type of medium used. Richard’s medium exhibited comparatively higher mycelial growth and sporulation for all the three test fungi, except P. psidii which preferred to grow on PDA in respective parameters. The poor performance of the three pathogens was recorded on Oatmeal and guava fruit extract media.